Journal Writing in the EFL Classroom of Nepal (Journal of NELTA, 2018)
Based on classroom research, this paper explores the use of journal writing as a multi-purpose tool in the English as a foreign language (EFL) classroom of Nepal. In the first part of the paper, the author introduces readers to the concepts of journal writing and also shares his own experience of writing reflective journals as a university student. This section also explains how he applied the same task among children in the classroom. The second part of the paper discusses the opportunities and challenges of using journal writing in the EFL classroom. The results suggest that journal writing can serve multiple purposes in the English language classroom. It is found to be an effective technique to make students reflect on what they have learnt and enhance their writing skill as well.Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, Page: 68-75